Representation of Power in the News Text of the Inclusion of Indigenous Faiths on ID Card (e-KTP) (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This paper presents the results of news analysis of the Supreme Court decision that Indigenous Faiths on the ID card (E-KTP) with Norman Fairclough's critical discourse analysis approach as the central platform. The study covers descriptions (text analysis), interpretations (discourse practices), and explanations (social practices). The results are as follows. (1) The structure of the news text Indigenous Faiths allowed on the ID card is built by four units of discourse: headline, orientation, the sequence of events, closing. Modalities and affirmative sentences represent the positive ideology of the conflicting faction and the institutions (government, scientists, and community leaders). Meanwhile, prohibiting speech and negative sentences represent the negative ideology. (2) What events occur, who is involved, what is the relationship with the issue raised, and what role the language can be expressed through the interpretation of the practice of discourse. (3) The situation when the news text is produced, the influence of the institution on the produced text, and the condition of Indonesians related to economic, political, social, and cultural interests (socio-cultural context).